High flexion knee arthroplasty: the relationship between rotational angles and flexion angle after total knee arthroplasty - Deie, Masataka (Springer US, 2014)
The current patients required high flexion total knee arthroplasty (TKA). We hypothesized the patients who would get the high rotational angle just after TKA could gain high flexion knee 1 year after TKA. Sixty-three patients (average age: 70.6 years) were examined. In order to examine between the intraoperative rotational angles and the gained flexion angles after TKA, the patients were divided into two groups: the H group (more than 120°) and the L groups (less than 120°) by the gained flexion angles. The relationship between the flexion angles at 1 year after surgery and the intraoperative rotational angle had no significant correlation. But the rotational angles in the L group tended to be higher than the ones in the H group, and at only 30°, the L group gained significantly more rotational angle than the H group. These results might show that a tighter rotational stability induces a gain of higher flexion knee after TKA.